Experiências de bullying escolar de estudantes com transtorno do espectro autista - Menezes, Regiane Silva de (2021)
The term bullying has been described as aggressive behavior that involves three fundamental criteria: repetition (aggressions are systematic), intentionality and imbalance/unequal power between aggressor and victim, who cannot defend themselves, as defined by Olweus & Smith. According to Smith, the psychosocial characteristics of individuals with autism spectrum disorder, such as lack of social skills and difficulties in expressing non-verbal forms of communication, can increase their vulnerability to bullying. Studies show that bullying generates some harmful consequences in victims, such as psychosomatic problems, depression, poor academic performance, impaired mental development and increased probability of psychosis. It ends up becoming a public health problem that requires scientific and political investments. Considering the scientific weaknesses and the impact on the health of children and adolescents, it is necessary to propose studies in order to understand the elements that contribute to the spread of the phenomenon and to propose possibilities for intervention, as pointed out by Marcolino. In this context, this study addresses the theme "School bullying experiences of People with Autistic Spectrum Disorder" and aimed to understand a social complex that are experiences of school bullying experienced by people diagnosed with ASD. It is based on qualitative, exploratory research, using multiple case studies, such as the Yin project. Each case was analyzed through data triangulation, adopting the Convergence of Multiple Data Sources model. As tools for this collection, semi-structured interviews were carried out with students diagnosed with autism spectrum disorder, parents, siblings and teachers and to find out about the understanding of bullying of students with ASD, the cartoon test developed by Smith was used. The sample collection technique used was a snowball sampling, to access the target audience of Virtual Social Networks (VSN). The results of this call attention to the importance of the research students' account, for the choice of people who hinder the inclusion and social process of people with research. It was possible that the difficulties in the minds of people who may be able to face school bullying, that coping strategies are developed in the minds of people with autism in order to improve their social relationships and their better understanding of social histories, the best would help to face the situations and minimize the damage to victims' stories.